Physiological behavior of bean (phaseolus vulgaris l.) Seedlings under metal stress - Zengin, Fikriye (Soc Biolgia Chile, 2013)
The effects of nickel, cobalt, chromium and zinc on the content of vitamins A, E and C, malondialdehyde (MDA), chlorophyll and carotenoids were investigated in bean seedlings (Phaseolus vulgaris L.) grown in Hoagland solution Control and heavy metal-treated plants were grown for ten days in Hoagland solution. Vitamin A, E, and C content were measured in primary leaves by high performance liquid chromatographic (HPLC). MDA, chlorophyll and carotenoids were measured in leaves by spectrophotometer. In heavy metal treated plants, the levels of MDA, vitamins A, E and C and carotenoids significantly increased, while chlorophyll content decreased in leaves of seedlings. The results indicate that heavy metals caused an oxidative stress in bean plants. The strongest effect on vitamins A, E and C, MDA, chlorophyll and carotenoids was found in plants exposed to nickel, followed by the sequence cobalt >chromium> zinc.
Keywords: Heavy metal; vitamins A, E and C; MDA; chlorophyll and carotenoids